Isoflurane increases the activity of the vascular matrix metalloproteinase-2 in non-pregnant rats and increases the nitric oxide metabolites in pregnancy - Souza, Carolina Rosa Rodrigues [UNESP]; Caetano, Edileia Souza Paula [UNESP]; Rodrigues, Serginara David [UNESP]; Lopes, Matheus Cleto [UNESP]; Mattos, Bruna Rahal; Santos, Mariana Landenberger; Rizzi, Elen; Dias, Carlos A. [UNESP] (Portland Press, 2024)
Surgeries that require general anesthesia occur in 1.5–2% of gestations. Isoflurane is frequently used because of its lower possibility of affecting fetal growth. Therefore, we examined the isoflurane anesthesia-induced effects on maternal hemodynamic and vascular changes. We hypothesized that isoflurane would enhance endothelium-dependent vasodilation as a consequence of increased nitric oxide and decreased metalloproteinases (MMPs). Female rats (n=28) were randomized into 4 groups (7 rats/group): conscious (non-anesthetized) non-pregnant group, non-pregnant anesthetized group, conscious pregnant group, and pregnant anesthetized group. Anesthesia was performed on the 20th pregnancy day, and hemodynamic parameters were monitored. Nitric oxide metabolites, gelatinolytic activity of MMP-2 and MMP-9, and the vascular function were assessed. Isoflurane caused no significant hemodynamic changes in pregnant compared with non-pregnant anesthetized group. Impaired acetylcholine-induced relaxations were observed only in conscious non-pregnant group (by approximately 62%) versus 81% for other groups. Phenylephrine-induced contractions were greater in endothelium-removed aorta segments of both pregnant groups (with or without isoflurane) compared with non-pregnant groups. Higher nitric oxide metabolites were observed in anesthetized pregnant in comparison with the other groups. Reductions in the 75 kDa activity and concomitant increases in 64 kDa MMP-2 isoforms were observed in aortas of pregnant anesthetized (or not) groups compared with conscious non-pregnant group. Isoflurane anesthesia shows stable effects on hemodynamic parameters and normal MMP-2 activation in pregnancy. Furthermore, there were increases in nitric oxide bioavailability, suggesting that isoflurane provides protective actions to the endothelium in pregnancy.